Battery plug-in electric vehicle concept design: design and integration of extendable solar roof - Tan, Chuan Yeow (2018)
This Final Year Project provided a documentation of the troubleshooting of the previous solar roof system and the design and manufacturing of its second version. The author was responsible to improve the structure of solar roof system version 1and eventually implemented the system on to the roll bar of Nanyang Venture 7. The objective of this project was to design, manufacturing and assembling a proper functioning deployable solar roof system and proceeded to implement it on to Nanyang Venture 7. The author initially started from analysis the issues happened on the design of version 1. After a series of troubleshooting, the author had proposed an improved version of solar roof system by redesigning the deployable mechanism and improving the structure rigidity. Fabrication of the components had proceeded after finalised the design and followed by assembly process. Demonstration of the deploy mechanism was performed after the solar panel was installed on the car. The report comprises of troubleshooting of problems on solar roof system version 1. Improvements were achieved to eliminate those problems and research on deploying mechanism was conducted to find a suitable deploy mechanism for the improved solar roof version. This report contained the detail design of the system with calculation and the process to manufacture it.